PERAN KOMPOSISI MINERAL PADA AIR GAMBUT DALAM MEMPERCEPAT REAKSI PEMBENTUKAN GAS HIDROGEN PADA PROSES ELEKTROLISIS - Musthofa, Imron; Artika, Kurnia Dwi; Hairiyah, Nina; Nugraheni, Ika Kusuma (Jurnal Rekayasa Mesin, 2025)
The existence of peatlands in Indonesia is quite extensive, but many peatlands in Indonesia are not utilized properly. So, peatlands are left as is. The low pH value of peatlands makes it very difficult to use peatlands as agricultural land and can only be planted with grass and other wild plants. Apart from that, the air from peatlands is also very abundant and of course cannot be used for consumption because the pH level is low, ranging from 3.2–4.7. Due to its low pH value, peat water also contains various metallic minerals such as Na, Mg, Al, Fe, Ca, K, and others. The mineral compounds contained in peat water indirectly produce electrolyte properties and can be used as a catalyst to speed up the reaction to produce hydrogen gas using the electrolysis method. The use of peatlands in South Kalimantan as a source of renewable energy, especially in its use as a source of hydrogen gas, is an innovative concept in providing alternative energy potential to support sustainable development. In the electrolysis process, peat water can produce an electrical voltage of 12 V which flows through the cathode and anode. From the results of research that has been carried out, the highest hydrogen gas productivity value in the M4 variable is 29 mL. This is influenced by the number of minerals in the composition of peat water. The highest electric current flowing was 0.17 A, and the highest power produced was 2.1 watts for an electrolysis time of 20 minutes.